2003
DOI: 10.1115/1.1580847
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Slug Dissipation and Generation in Gas-Liquid Hilly-Terrain Pipe Flow

Abstract: Hilly-terrain pipelines consist of interconnected horizontal, uphill and downhill sections. Slug flow experiences a transition from one state to another as the pipe inclination angle changes. Normally, slugs dissipate if the upward inclination becomes smaller or the downward inclination becomes larger, and slug generation occurs vice versa. Appropriate prediction of the slug characteristics is crucial for the design of pipeline and downstream facilities. In this study, slug dissipation and generation in a vall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…To that end, models that track the front and back of individual slugs can be used to evaluate their characteristic lengths. For details on this approach, refer to the models of Al-Safran et al (2004) and Zhang et al (2003), which resort to the first principles for flow description. The unsteady velocity behavior of newly initiated slugs was investigated in Al-Safran et al (2013).…”
Section: Unit-cell Models For Slug Flow Predictionmentioning
confidence: 99%
“…To that end, models that track the front and back of individual slugs can be used to evaluate their characteristic lengths. For details on this approach, refer to the models of Al-Safran et al (2004) and Zhang et al (2003), which resort to the first principles for flow description. The unsteady velocity behavior of newly initiated slugs was investigated in Al-Safran et al (2013).…”
Section: Unit-cell Models For Slug Flow Predictionmentioning
confidence: 99%
“…The uneven seafloor topography results in hilly-terrain pipeline/riser systems. A hillyterrain pipeline consists of interconnected horizontal, downhill, and uphill sections (Zhang et al 2003). Although flow instabilities are relatively well understood for downward and horizontal pipeline/riser configurations (e.g., see Malekzadeh et al 2012b), there is still a lack of understanding of how flow characteristics change in a hilly-terrain pipeline/riser system.…”
Section: Introductionmentioning
confidence: 99%
“…He observed slug flow behavior in a hilly-terrain pipeline, including generation of pseudo slugs at the horizontal/uphill elbow, variation of slug length along the pipeline, and existence of slug flow in the downhill section. In previous studies by Zhang et al (2003) and Al-Safran (2003) for two-phase hilly-terrain pipelines, the flow behavior in the elbow of the hilly-terrain section was coupled and analyzed with the flow conditions in the upstream downhill and downstream uphill sections of the hilly-terrain unit. Al-Safran et al (2005) also identified five different categories for slug dissipation in downhill section and slug initiation and growth in the uphill section of a hilly-terrain pipeline: (1) complete dissipation in the downhill section with slug initiation at the dip, (2) no hilly-terrain effect, (3) partial dissipation in the downhill section with initiation and growth at the dip, (4) no dissipation in the downhill section with initiation and growth at the dip, and (5) no dissipation in the downhill section with growth only at the dip.…”
Section: Introductionmentioning
confidence: 99%